Предмет: Алгебра,
автор: malaya290
помогите решить
7•(2х-3)+4•(3х-2)=
(3х-11)•2-5(4-3х)=
Ответы
Автор ответа:
0
7•(2х-3)+4•(3х-2)=
=(14х-21) + (12х-8)=
14х+12х=21+8
26х=29
х=29-26
х=3
(3х-11)•2-5(4-3х)=
=(6х-22)-(20-15х)=
9х=42
х=33
надеюсь правильно решил))
=(14х-21) + (12х-8)=
14х+12х=21+8
26х=29
х=29-26
х=3
(3х-11)•2-5(4-3х)=
=(6х-22)-(20-15х)=
9х=42
х=33
надеюсь правильно решил))
Автор ответа:
0
спасибо огромное
Похожие вопросы
Предмет: Биология,
автор: clown51
Предмет: Алгебра,
автор: Аноним
Предмет: Музыка,
автор: liza121366
Предмет: Математика,
автор: 898986